High-throughput physical map anchoring via BAC-pool sequencing - Cviková, Kateřina; Cattonaro, Federica; Alaux, Michael; Stein, Nils; Mayer, Klaus Fx; Doležel, Jaroslav; Bartoš, Jan (BMC plant biology, 2015)
BACKGROUND: Physical maps created from large insert DNA libraries, typically cloned in BAC vector, are valuable resources for map-based cloning and de novo genome sequencing. The maps are most useful if contigs of overlapping DNA clones are anchored to chromosome(s), and ordered along them using molecular markers. Here we present a novel approach for anchoring physical maps, based on sequencing three-dimensional pools of BAC clones from minimum tilling path. RESULTS: We used physical map of wheat chromosome arm 3DS to validate the method with two different DNA sequence datasets. The first comprised 567 genes ordered along the chromosome arm based on syntenic relationship of wheat with the sequenced genomes of Brachypodium, rice and sorghum. The second dataset consisted of 7,136 SNP-containing sequences, which were mapped genetically in Aegilops tauschii, the donor of the wheat D genome. Mapping of sequence reads from individual BAC pools to the first and the second datasets enabled unambiguous anchoring 447 and 311 3DS-specific sequences, respectively, or 758 in total. CONCLUSIONS: We demonstrate the utility of the novel approach for BAC contig anchoring based on mass parallel sequencing of three-dimensional pools prepared from minimum tilling path of physical map. The existing genetic markers as well as any other DNA sequence could be mapped to BAC clones in a single in silico experiment. The approach reduces significantly the cost and time needed for anchoring and is applicable to any genomic project involving the construction of anchored physical map.
Keywords: High-Throughput Nucleotide Sequencing; vysoce účinné nukleotidové sekvenování; Chromosome Mapping; umělé bakteriální chromozomy; Plants; rostliny; chromozomy rostlin; Chromosomes, Artificial, Bacterial; Chromosomes, Plant; mapování chromozomů